A Proposed Accounting Model to Measure and Evaluate the Sustainable Performance of Companies Based on Lean Production (International Journal of Financial, Administrative and Economic Sciences, 2023)
This study aims to provide a real justification for the use of a measurement and evaluation model for the sustainable performance of lean production. This study confirms the main justification for using and applying this model in organizations. It is considered an integrated and comprehensive system for measuring and evaluating sustainable performance. This study also illustrates the role of the model in linking the general strategy to the organization's operational strategy. There are three basic steps to follow in building a model for achieving sustainable development: implementing a sustainable performance model; Building and applying the proposed model; and determining the target outputs of the proposed model. This study concluded that the most important basic factors for building and implementing the proposed model are related to organizational culture and managing relationships with various parties, such as senior management, shareholders, customers, workers, suppliers, legislators, and society. Due to the many impacts on sustainability during the product life cycle, organizations are only concerned with the production phase. Therefore, lessons can be learned from other industrial environments by dividing organizations into numerous administrative processes and units. From a practical standpoint, the study tested the validity of the model for economic, environmental, and social performance to obtain an indicator that demonstrates sustainable performance and the achievement of the sustainable development strategy.
Keywords: Accounting Model; Sustainable Performance; Lean Production Model; Lean Services Model